2010
DOI: 10.1094/pdis-94-9-1156
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Responses of Resistant and Susceptible Olive Cultivars Induced by Defoliating and Nondefoliating Verticillium dahliae Pathotypes

Abstract: Verticillium wilt is the most serious olive disease worldwide. The olive-infecting Verticillium dahliae pathotypes have been classified as defoliating (D) and nondefoliating (ND), and the disease is mainly controlled in olive orchards by using resistant or tolerant cultivars. Limited information is available about the nature of resistance in most of the olive cultivars. In the present study, the phenolic responses of the susceptible to V. dahliae olive cv. Amfissis and the resistant cv. Koroneiki upon D and ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 35 publications
3
60
2
Order By: Relevance
“…However, little is known on mechanisms responsible of the wilting syndrome or on host defense responses in olive upon V. dahliae infection with the exception of those reported by Baídez et al (2007) and by Markakis et al (2010). Nevertheless, physiological alterations as a consequence of pathogen invasion may have a strong influence on photosynthesis, nutrient translocation, water transport, and/or respiration as described in other hosts (Abeles et al 1992;Resende et al 1996;Sadras et al 2000).…”
Section: Verticillium Wilt Of Olive Disease Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known on mechanisms responsible of the wilting syndrome or on host defense responses in olive upon V. dahliae infection with the exception of those reported by Baídez et al (2007) and by Markakis et al (2010). Nevertheless, physiological alterations as a consequence of pathogen invasion may have a strong influence on photosynthesis, nutrient translocation, water transport, and/or respiration as described in other hosts (Abeles et al 1992;Resende et al 1996;Sadras et al 2000).…”
Section: Verticillium Wilt Of Olive Disease Cyclementioning
confidence: 99%
“…quercetin, luteolin or rutin) present in olive were suggested to act as phytoanticipins and/or phytoalexins of olive's natural defense or resistance mechanisms (Baídez et al 2007). Recently, Markakis et al (2010) have reported the involvement of verbascoside in defense mechanisms of Greek olive cultivars against V. dahliae.…”
Section: Verticillium Wilt Of Olive Disease Cyclementioning
confidence: 99%
“…For example, some phenolic derivatives can react with pathogen proteins, causing loss of their enzymatic functions thus suppressing pathogen viability (Markakis et al 2010). The flavonoids were described as having antibacterial, antitoxin, antiviral and/or antifungal activities and as being involved in structural defense (Treutter 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known about biochemical and molecular mechanisms of olive resistance to the Verticillium wilt. Among investigated aspects, it seems to be very important the role of phenolic methabolism (Baidez et al, 2007;Markakis et al, 2010). Vizzarri et al (2011) investigated the susceptibility of cvs.…”
Section: Resistance To Verticillium Dahliaementioning
confidence: 99%
“…Koroneiki showed higher increasing of phenols than susceptible cv. Amfissis when inoculated with verticillium wilt (Markakis et al, 2010). Genes PAL e CHS play an important role in the biosynthesis of phenolic compounds, then a role in determing resistance of olive cultivars to verticillium wilt could be hypothesised.…”
Section: Resistance To Verticillium Dahliaementioning
confidence: 99%